2007
DOI: 10.1001/archpsyc.64.6.633
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Effects of Antipsychotic Medications in Patients With Chronic Schizophrenia in the CATIE Trial

Abstract: After 2 months of antipsychotic treatment, all groups had a small but significant improvement in neurocognition. There were no differences between any pair of agents, including the typical drug perphenazine. These results differ from the majority of previous studies, and the possible reasons are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
573
2
14

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 980 publications
(613 citation statements)
references
References 84 publications
18
573
2
14
Order By: Relevance
“…Reductions in GABAergic interneurones in these areas have been found in post-mortem analysis from patients with schizophrenia (Benes et al, 1991;Benes and Berretta, 2001;Beasley et al, 2002;Zhang and Reynolds, 2002). We have shown that atypical but not classical antipsychotics can reverse these cognitive deficits; however, in the clinic there is differing evidence for the efficacy of atypical antipsychotics in improving cognition with the CATIE study (Lieberman, 2006;Keefe et al, 2007) and the UK Cost Utility of the Latest Antipsychotic Drugs in Schizophrenia Study (CUtLASS; Jones et al, 2006; suggesting that antipsychotics actually have a limited effect. Cognitive dysfunction is a core characteristic of schizophrenia (Sullivan et al, 1994;Elvevag and Goldberg, 2000;Kuperberg and Heckers, 2000), occurring in 75-85% of patients (Reichenberg et al, 2006), and is becoming increasingly important as impaired cognition has been implicated in poor long-term functional outcome (Marder and Fenton, 2004) which can often persist when other symptoms may be improved with treatment (Gold et al, 1991;Heinrichs, 2005).…”
Section: Introductionmentioning
confidence: 81%
“…Reductions in GABAergic interneurones in these areas have been found in post-mortem analysis from patients with schizophrenia (Benes et al, 1991;Benes and Berretta, 2001;Beasley et al, 2002;Zhang and Reynolds, 2002). We have shown that atypical but not classical antipsychotics can reverse these cognitive deficits; however, in the clinic there is differing evidence for the efficacy of atypical antipsychotics in improving cognition with the CATIE study (Lieberman, 2006;Keefe et al, 2007) and the UK Cost Utility of the Latest Antipsychotic Drugs in Schizophrenia Study (CUtLASS; Jones et al, 2006; suggesting that antipsychotics actually have a limited effect. Cognitive dysfunction is a core characteristic of schizophrenia (Sullivan et al, 1994;Elvevag and Goldberg, 2000;Kuperberg and Heckers, 2000), occurring in 75-85% of patients (Reichenberg et al, 2006), and is becoming increasingly important as impaired cognition has been implicated in poor long-term functional outcome (Marder and Fenton, 2004) which can often persist when other symptoms may be improved with treatment (Gold et al, 1991;Heinrichs, 2005).…”
Section: Introductionmentioning
confidence: 81%
“…Specifically, clozapine has demonstrated limited or no effects on executive function (Meltzer and McGurk, 1999;Hoff et al, 1996;Bellack et al, 2004). Risperidone has been shown either to be not effective (Bellack et al, 2004;Remillard et al, 2005;Lee et al, 2007) or slightly effective, as measured by Wisconsin Card Sorting Test (Meltzer and McGurk, 1999;Harvey et al, 2005), and olanzapine produces effects in the same range as risperidone (Meltzer and McGurk, 1999;Bilder et al, 2002;Keefe et al, 2007). In a small clinical trial, sertindole has shown superiority to haloperidol on executive function performance (Gallhofer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Novel antipsychotic compounds (second-generation or 'atypical' antipsychotics) such as clozapine (Fitton and Heel, 1990), olanzapine (Fulton and Goa, 1997), and sertindole (Kane and Tamminga, 1997;Azorin et al, 2006) have some beneficial effect on negative symptoms and reduced potential to produce extrapyramidal side effects, but these agents have demonstrated inconsistent effects on cognitive function in patients with schizophrenia. Depending on the type of cognitive domain measured, second-generation antipsychotics have been reported to produce improvement (Mortimer 1997;Meltzer and McGurk, 1999;Keefe et al, 2007), no effect (Hoff et al, 1996;Meltzer and McGurk, 1999), and impairment (Goldberg et al, 1993). The effect of sertindole on cognitive function has not been investigated extensively; however, a small clinical trial indicates a beneficial effect on some cognitive substrates, including executive function, in individuals diagnosed with schizophrenia (Gallhofer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These deficits are present at disease onset (e.g., Saykin et al, 1994), stable over time (e.g., Gold et al, 1999;Hoff et al, 1999;Kurtz et al, 2005;Stirling et al, 2003), and are only modestly affected by pharmacologic intervention for symptoms (e.g., Harvey & Keefe, 2001;Keefe et al, 2007). Particular significance has been attached to these deficits, as there are a growing number of studies showing that deficits in elementary neurocognitive function are linked to a variety of aspects of functional outcome cross-sectionally and in some cases longitudinally as well.…”
Section: Introductionmentioning
confidence: 99%